Life management concepts of transformer investigations - Vinoth Kumar, K; Matthew Sam, Nithin; Sony, Kevin (International Journal of Engineering and Technology, 2018)
This paper shows the importance of specifications and life management concepts for reliable, uninterrupted and intended application of transformers throughout the life cycle. The transformers are tested, manufactured and designed based on the specification.